Antifertility activity of Cryptolepis sanguinolenta leaf ethanolic extract in male rats - Ayodeji F Ajayi; Roland E Akhigbe (Wolters Kluwer Medknow Publications, 2012)
Background: Complementary medicine has grown over time with more botanicals emerging and remaining integral parts of medicare. Such botanicals include Cryptolepis sanguinolenta. AIM: This study investigated the effect of Cryptolepis sanguinolenta leaf ethanolic extract on male reproductive system using rat model. Materials and Methods: Control and treated rats were maintained on control diet. Treated rats also received graded doses of the extract. RESULTS: When compared with the controls, Cryptolepis sanguinolenta treatment led to significant testosterone suppression associated with consequent significant rise in luteinizing hormone (LH) and decrease in sperm count. Treatment with Cryptolepis sanguinolenta did not result in significant attenuation of follicular stimulating hormone (FSH) levels and testicular morphometry. Sperm viability, motility, and morphology were also comparable in all groups. Conclusion: These results suggest that Cryptolepis sanguinolenta possesses anti-androgenic and anti-spermatogenic properties with potential anti-aphrodisiac activity.